FUNGSI PENGENDALI DAN PENGAMAN PENGGUNA JALAN DI KAB.PANGKEP : (PERSFEKTIF SIYASAH SYAR’IYYAH) - @fajriahrahmainaya, 23_fajrininaya23; Tenripadang, Andi (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2025)
his research aims to find out how the function of controlling and protecting road users in Kab. Pangkep (Siyasah Syariyyah Perspective). The main problem is divided into several sub-problems, namely: How useful is the safety control for road users in the district. Pangkep, what is the public’s view of road user safety in Pangkep Regency, and what is Siyasah Syar’iyyah’s view of controlling road users in Pangkep Regency. The research method used is data collection in the form of observation, interviews, documentation and reference tracking. The results of this research show that the benefits of road user safety controls are very beneficial for the community because people can pay attention to the direction of oncoming traffic, in order to reduce the occurrence of accidents, so it is necessary to install shock bands so that drivers are careful when driving. The public’s view of road user safety is that most drivers obey the rules and there are also those who break them, so the existence of these rules can provide regulations that can be set by the transportation service. Siyasah Syari’iyyah’s view of controlling road users is that it is described as a policy requirement to regulate state affairs based on sharia, therefore using public highways for personal gain is prohibited by Islamic law, so it is necessary to have several restrictions, so as to create benefits and prevent losses, which are not contrary to the provisions of Islamic sharia and general principles, which results in the problem of Murlah.